Pengembangan Video Pembelajaran Berbasis Model Problem Based Learning (PBL) Materi Siklus Air Kelas V SD untuk Meningkatkan Berpikir Kritis - Sari Erander; Endang Widi Winarni; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to determine the feasibility of the material, language, media, and student responses, as well as the effectiveness of the PBL model-based learning video development product effectiveness to improve critical thinking in elementary school science learning. This research is a Research and Development (R&D) research. The model used in the development is a 4-D model. The subjects in the study were students of SDN 63 Lubuklinggau, totaling 21 students of class VA as the control class, and 25 students of class V B as the experimental class. The instrument used in this research is an interview guide, a questionnaire, and a test of understanding this concept in the form of essay questions through pretest and posttest. To measure the effectiveness of concept understanding, two tests were conducted, namely before and after the learning took place in the experimental class and the control class. The data analysis technique in this study is validation analysis using Aiken's V and Interrater Reliability, teacher and student responses, and quantitative analysis using N-gain. From the research results, it is known that the results of material, language, and design validation, as well as student responses to learning videos are very feasible and good for use in learning so that students are happy and interested in learning. The results of the effectiveness of effective learning videos affect students' understanding of science concepts. Based on the gain-score test from the learning video, it gives a moderate gain score of 66%. So that students' understanding of science concepts who use PBL-based learning videos to improve critical thinking is higher than students who only use textbooks from school so that they are declared effective.